High-throughput detection of potential bacteriocin producers in a large strain library using live fluorescent biosensors - Otto, Sebastian J.; Teichmann, Laura; Fante, Niklas; Crauwels, Peter; Grünberger, Alexander; Neddermann, Tobias; Riedel, Christian U. (Frontiers in Bioengineering and Biotechnology, 2024)
The global increase in antibiotic resistances demands for additional efforts to identify novel antimicrobials such as bacteriocins. These antimicrobial peptides of bacterial origin are already used widely in food preservation and promising alternatives for antibiotics in animal feed and some clinical setting. Identification of novel antimicrobials is facilitated by appropriate high throughput screening (HTS) methods. Previously, we have described a rapid, simple and cost-efficient assay based on live biosensor bacteria for detection of antimicrobial compounds that act on membrane integrity using the ratiometric pH-dependent fluorescent protein pHluorin2 (pHin2). Here, we use these biosensors to develop an integrated pipeline for high-throughput identification of bacteriocin producers and their biosynthetic gene clusters. We extend the existing portfolio of biosensors by generating pHin2 expressing strains of Escherichia coli, Bacillus cereus, Staphylococcus epidermidis, and methicillinresistant Staphylococcus aureus. These strains were characterized, and control experiments were performed to assess heterogeneity of these biosensors in response to known bacteriocins and develop a robust HTS system. To allow detection of compounds that inhibit target bacteria by inhibiting growth without disturbing membrane integrity, the HTS system was extended with a growth-dependent readout. Using this HTS system, we screened supernatants (SNs) of a total of 395 strains of a collection of lactic acid bacteria. After 2 rounds of screening 19 strains of the collection were identified that produced antimicrobial activity against Listeria innocua and Listeria monocytogenes. Genomes of confirmed hits were sequenced and annotated. In silico analysis revealed that the identified strains encode between one and six biosynthetic gene clusters (BGCs) for bacteriocins. Our results suggest that pHin2 biosensors provides a flexible, cheap, fast, robust and easy to handle HTS system for identification of potential bacteriocins and their BGCs in large strain collections.